2017
DOI: 10.1177/0284185117725369
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of variability in breast density assessment by BI-RADS category according to the level of experience

Abstract: Background Only few studies have assessed variability in the results obtained by the readers with different experience levels in comparison with automated volumetric breast density measurements. Purpose To examine the variations in breast density assessment according to BI-RADS categories among readers with different experience levels and to compare it with the results of automated quantitative measurements. Material and Methods Density assignment was done for 1000 screening mammograms by six readers with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…However, there was no evidence indicating that the consistency changed as a result of different experience levels. Eom et al (31) conducted their study, which used similar methodology with six readers and three different levels of experience (two breast imaging experts, two general radiologists, and two medical students) and showed substantial to near-perfect intra-reader agreement when using the BI-RADS 5th edition. They also found no statistically significant difference with regard to the different levels of experience for the intra-reader agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no evidence indicating that the consistency changed as a result of different experience levels. Eom et al (31) conducted their study, which used similar methodology with six readers and three different levels of experience (two breast imaging experts, two general radiologists, and two medical students) and showed substantial to near-perfect intra-reader agreement when using the BI-RADS 5th edition. They also found no statistically significant difference with regard to the different levels of experience for the intra-reader agreement.…”
Section: Discussionmentioning
confidence: 99%
“…They also found no statistically significant difference with regard to the different levels of experience for the intra-reader agreement. Additionally, they studied the agreement between the Volpara automated volumetric breast density measurements and those obtained using the BI-RADS; they found that expert radiologists showed higher consistency with regard to the volumetric and qualitative assessments than did the students (31).…”
Section: Discussionmentioning
confidence: 99%
“…By using 2D mammograms MDs breasts are classified based on thorax density as: (a) entirely fatty, (b) scattered areas of fibroglandular density, (c) heterogeneously dense, and (d) extremely dense. It is important to note that this method is based on MDs in 2D measures, and that it can be wrong if it is done in 3D systems [16][17][18]. Because of this, all the results have been done inside a 2D system, and measured in 2D working domain.…”
Section: Imaging Biomarkers (Bi)mentioning
confidence: 99%
“…This visual assessment is clinically useful, but it can vary based on the physician's training and can be inaccurate compared with 3-D measures. [252][253][254] This leaves greater chance for error in patient care. [252][253][254] By comparison, a quantitative imaging biomarker (QIB) is an objective characteristic derived from an in vivo image measured on a ratio or interval.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…[252][253][254] This leaves greater chance for error in patient care. [252][253][254] By comparison, a quantitative imaging biomarker (QIB) is an objective characteristic derived from an in vivo image measured on a ratio or interval. 8 CADe and CADx algorithms use QIB, and trials have demonstrated that they can improve radiologist performance.…”
Section: Imaging Biomarkersmentioning
confidence: 99%